Characteristics of the Ionosphere at Washington, D.C., April 1938 - Gilliland, T.R.; Kirby, S.S.; Smith, N. (Proceedings of the Institute of Radio Engineers, 1938)
Data on the ordinary-wave critical frequencies and virtual heights of the ionospheric layers are presented for the period indicated in the title. The monthly average values of the maximum usable frequencies for undisturbed days, for radio transmission by way of the regular layers is also provided.